A Philosophical Essay on Molecular Structure - Hirofumi, Ochiai (Cambridge Scholars Publisher, 2021)
Molecular structure is something taken for granted by chemists. Together with elements, atoms and bonds, it is the basis for talking about organic chemistry. Given molecular structure, chemists are engaged in designing molecules and performing chemical syntheses of a variety of compounds. The structure-activity relationship in drug research is an illuminating example. However, of course, nobody has ever seen molecular structure. Molecules are too small to see. Moreover, molecular structure cannot be derived a priori from fundamental principles of quantum mechanics. This book explores why this.